The singularity response reveals entrainment properties of the plant circadian clock - Kosaku Masuda (Nature Portfolio, 2021)
Phase response curves reveal how biological clocks respond to stimuli applied during different circadian phases but can be costly to produce. Here Masuda et al. show that phase response curves for plants can be reconstructed by monitoring how a desynchronized population responds to a single stimulus.